Survey of arthropofauna from riparian areas in a sector of the Tapia and Vipos rivers (Tapia-Trancas watershed, Tucuman, Argentina) - Hill, Jorge Guillermo (2017)
Riparian habitats allow the maintenance of water quality, protecting wildlife and the formation of natural corridors. Currently, terrestrial arthropofauna is poorly known in these kinds of habitats and, even more, the lack of information is higher for riparian areas belonging to the Semi-arid Chaco ecoregion. Therefore, the aims of this study were to conduct a survey of arthropods present in habitats associated with Tapia and Vipos rivers (Tucuman); and to identify at the family level the two most abundant orders within the Insecta class, diversity for each group being estimated. Sampling was conducted during the months of April and May 2014, in two sections of the Tapia and Vipos rivers. Specimens were collected with Moericke traps (yellow pan traps). A total of 1,861 individuals were surveyed, Collembola being the most numerous taxa (37.5%). Within the Insecta class, 994 individuals belonging to nine orders were collected, out of which the most abundant ones were the Hymenoptera (38.9%) and Diptera (31.7%) orders. In the Hymenoptera, a total of 24 families were recorded, Formicidae being the prevalent frequent family (96 individuals followed by Encyrtidae (52 individuals). In the Diptera order, a total of 23 families were identified, the Phoridae family being the bestl represented (96 individuals), followed by Dolichopodidae (59 individuals), and thirdly Sciaridae (50 individuals). This study represents the first descriptive work for terrestrial arthropofauna associated with riparian ecosystems of Semi-arid Chaco ecoregion of the Tucuman province.